DSM-5 made easy : the clinician's guide to diagnosis - Morrison, James R., 1940- (New York : The Guilford Press, 2014)
Morrison presents the spectrum of diagnoses in DSM-5 in an accessible, engaging, clinically useful format. Demystifying DSM-5 criteria without sacrificing accuracy, he includes both ICD-10-CM and ICD-9-CM codes for each disorder, as well as the Global Assessment of Functioning (GAF) Scale (from DSM-IV-TR), with a clear rationale for its continued use. Discussions of sample cases demonstrate how to arrive at the diagnosis and rule out other likely possibilities.
Neurodevelopmental disorders -- Schizophrenia spectrum and other psychotic disorders -- Mood disorders -- Anxiety disorders -- Obsessive-compulsive and related disorders -- Trauma- and stressor-related disorders -- Dissociative disorders -- Somatic symptom and related disorders -- Feeding and eating disorders -- Elimination disorders -- Sleep-wake disorders -- Sexual dysfunctions -- Gender dysphoria -- Disruptive, impulse-control, and conduct disorders -- Substance-related and addictive disorders -- Cognitive disorders -- Personality disorders -- Paraphilic disorders -- Other factors that may need clinical attention -- Patients and diagnoses.
Includes bibliographical references and index.
Keywords: Mental Disorders -- diagnosis -- case reports; Mental Disorders -- classification -- Case Reports